"This Vilest of Trades": The League of Nations Anti-Trafficking Inquiry of 1927 - Jensen, Sebastian Vang (Culture and History: Student Research Papers, 2023)
This article examines the League of Nations’ official inquiry into the international question of trafficking, integral to their wider anti-trafficking campaign of the 1920’s. Through this, it assesses the consequences of employing external experts drafted from activist non-governmental organizations to conduct large-scale international research projects. In doing so it argues that the League’s official standards of unbiased data collection and knowledge production was somewhat compromised and that the leaders of the external research group used this official inquiry as a form of trojan horse to challenge and undermine the legitimacy of the system of regulated prostitution. Furthermore, this article unfolds how the research constructed new systems of knowledge about the nature of prostitution, that in turn positioned the system as a global threat with the potential to degenerate the future of humanity.